BENTUK DAN FUNGSI JARANAN BUTO CAMPURSARI LANGGENG BUANA DESA TEGALARUM BANYUWANGI - Hidayah, Nikmatul; Suharti, Mamik (Institut Seni Indonesia Surakarta, 2023)
Jaranan Buto Campursari is a folk dance found in the Tegalarum Village area, Sempu District, Banyuwangi Regency. Jaranan Buto Campursari has undergone several changes both in terms of name and presentation. This is due to the need for presentation so that it is not monotonous. Previously, the name Jaranan Buto did not use the name Campursari, but Setro Asnanwi added the name Campursari because the form of presentation included the presentation of other dances. As it developed, Jaran Buto Campursari changed its name to Jaranan Buto Campursari Langgeng Buana. This research aims to describe the form and function of Jaranan Buto Campursari which lives and develops in Tegalarum Village, Sempu District, Banyuwangi. Jaranan Buto Campursari is one of the folk dances in the Langgeng Buana art group which is danced in groups. The main problems in this research consist of 2 (two) first, what is the form of Jaranan Buto Campursari, the second is how Jaranan Buto Campursari functions. This research uses the theory of form and function. The theory of form comes from Y. Sumandyo Hadi and the theory of function uses theory from Soedarsono. This research is qualitative in nature through the stages of observation, interviews, documentation and literature study, as well as using data analysis. The results of this research show that the Jaranan Buto Campursari dish consists of 2 parts, namely pre-performance and performance. The author reveals the form and function of Jaranan Buto Campursari. Form includes the structure of the presentation and the elements of the performance. The Jaranan Buto Campursari performance has several functions that influence society. Among them as a means of ceremonies, as personal entertainment and as a spectacle for the local community. Apart from that, Jaranan Buto Campursari has an influence on the economy of the people of Tegalarum Village and its surroundings.